Evaluation of the Implementation of Crime Prevention Strategies of the Philippine National Police in Ormoc City, Leyte in the Context of the Covid-19 Pandemic - Molas, Nancy Hernando; Hernando, Loela Elisan; Mallorca, Hessimae Sanoria; Ceniza, Marie Regulacion; Malang, Bernandino P.; Vigonte, Florinda G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The COVID-19 Pandemic had made the Philippines to face various expanding crime rates which became a valuable issue in the country. These wrongdoings had operationally pushed the Philippine National Police to see and assess different crime activities that had been concurring consistently. This made the PNP to established community public security which then is called to be crime prevention strategies. This confronts the transition of different conflicting state including actions that inflicts harm to the populace. However, the known implemented strategies were not observed whether these promotes consistent advantage security or implementation were not addressed properly. Therefore, this study aims to determine the evaluation of the implementation of crime prevention strategies of the Philippine National Police in Ormoc City, Leyte in the Context of the COVID-19 Pandemic. A descriptive quantitative was used in purposive sampling was employed to obtain the 125 respondents of the study mainly PNP personnel and barangay captain. A self-constructed questionnaire with 4-point Likert scale has undergone a pilot study among 25 known respondents wherein the actual run was done through online survey. The result had shown that indicators including the crime prevention activities as to prevention strategies shows no significant differences. However, sustainability of the strategies establishes relationship with the demographic profile. Therefore, the study had concluded that the null hypothesis must be accepted which pertains that the strategies of the PNP towards crime prevention is not highly significant with the demographic profile.